INCREASING MATHEMATICAL PROBLEM SOLVING SKILLS THROUGH CORE LEARNING APPLICATION TO JUNIOR HIGH SCHOOL STUDENTS - Nuning Purwanti; Lukman Ibrahim; Novi Trina Sari (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
The purpose of this study is to find the mathematical problem solving abilities of junior high school students who are taught between the CORE model and conventional learning, increase students' mathematical problem solving abilities after implementing the CORE model. The research method used was experimental research with a pretest-posttest control group design. The population in this study were all students of SMP Negeri 3 Meulaboh, with sampling carried out using simple random sampling techniques. In this study the sample consisted of two classes, namely VIII4 as the experimental class and VIII6 as the control class. From the research results, it was obtained (1) the mathematical problem solving abilities of students who were taught the CORE learning model were better than conventional learning, this could be obtained from the t-test statistical data with t-count = 3.45 and t-table = 1.67. (2) increase in mathematical problem solving abilities of class VIII students of SMP Negeri 3 Meulaboh who are taught through the CORE learning model,13,86 1,67. Thus rejected, which means acceptedTherefore, it can be concluded that there isincreasing students' mathematical problem solving abilities through the application of the CORE learning model to junior high school students.